Systematic review of the pharmacological agents that have been tested against spreading depolarizations - Klass, Anna; Sánchez-Porras, Renán; Santos, Edgar (Journal of cerebral blood flow & metabolism, 2018)
Spreading depolarization (SD) occurs alongside brain injuries and it can lead to neuronal damage. Therefore, pharmacological modulation of SD can constitute a therapeutic approach to reduce its detrimental effects and to improve the clinical outcome of patients. The major objective of this article was to produce a systematic review of all the drugs that have been tested against SD. Of the substances that have been examined, most have been shown to modulate certain SD characteristics. Only a few have succeeded in significantly inhibiting SD. We present a variety of strategies that have been proposed to overcome the notorious harmfulness and pharmacoresistance of SD. Information on clinically used anesthetic, sedative, hypnotic agents, anti-migraine drugs, anticonvulsants and various other substances have been compiled and reviewed with respect to the efficacy against SD, in order to answer the question of whether a drug at safe doses could be of therapeutic use against SD in humans.
Gesehen am 28.10.2019